2020
DOI: 10.1186/s42269-020-00362-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of storage periods and positioning during storage on hatchability and weight of the hatched chicks from different egg sizes

Abstract: Background: This study evaluates the effects of storage periods (1, 4, 7, 10, and 13 days), egg size (small 60-64 g, medium 65-69 g, and large ≥ 70 g), and egg positioning with air cell facing either down or up during storage on hatchability percentages and day-old chick's weight. One thousand and five hundred (1500) fertile eggs from Arbor acre broiler breed were purchased and arranged each according to egg sizes into five (5) different storage periods of 100 eggs per storage period. Each storage period was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…Transylvanian naked neck chicken eggs seem to be highly sensitive to storage extension, in that storage for 3, 6, and 9 d had already caused a reduction of 18.2, 40.4, and 42.5%, respectively. Usually, hatchability in chicken eggs increases slightly to reach a peak between 3 and 5 d after oviposition ( Addo et al, 2018 ; Ayeni et al, 2020 ; Nasri et al, 2020 ; Rahardja et al, 2020 ; Abioja et al, 2021 ). Thereafter, further storage causes steady reduction in egg hatchability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transylvanian naked neck chicken eggs seem to be highly sensitive to storage extension, in that storage for 3, 6, and 9 d had already caused a reduction of 18.2, 40.4, and 42.5%, respectively. Usually, hatchability in chicken eggs increases slightly to reach a peak between 3 and 5 d after oviposition ( Addo et al, 2018 ; Ayeni et al, 2020 ; Nasri et al, 2020 ; Rahardja et al, 2020 ; Abioja et al, 2021 ). Thereafter, further storage causes steady reduction in egg hatchability.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the present findings, other authors reported consistent decline in hatchability without any peak as eggs increased in days post-oviposition ( Khan et al, 2013 , 2014 ). It may be more economical to limit storage of TNN eggs to 3 d, or at most 4 or 5 d if other intervention could be put in place Ayeni et al (2020) . limited days of egg storage to 4 d for optimum hatchability while Khan et al (2014) pegged it at 3 d.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors found similar results for eggs stored with pointed end up with regard to hatchability and embryonic mortality [4,11,27]. These significant differences between egg position groups disappeared after 21 days of storage period.…”
Section: Egg Positionmentioning
confidence: 53%
“…Despite the fact that egg storage time is known not to exceed 1 week in the poultry industry [2] which was probably due to albumen degradation with longer storage period [4]; many researchers have proved partridge eggs are more durable to longer storage period [5][6][7]. According to Caglayan, Alasahan [6], the internal quality of partridge eggs was deteriorated by long storage time.…”
Section: A C C E T E Dmentioning
confidence: 99%
See 1 more Smart Citation